Bodily Learning Through Creating Dance: Student Teachers' Experiences From Norwegian Physical Education Teacher Education - Ørbæk, Trine (Frontiers in Sports and Active Living, 2021)
Creating dance in physical education teacher education (PETE) is described as a way of expressing subjective experiences based on movements that the students have already mastered or as a way of composing dance with set movements from various dance forms that are further explored through concepts such as time, space, power and flow. This article shows how 13 Norwegian student teachers experienced the creation of dance as part of their PETE. It explores the following questions: how do student teachers in PETE experience dance creation as an embodied process of exploring, transforming and creating movements, and how were these experiences facilitated by bodily learning that was initiated by body memories? The results show that creating dance is a intersubjective, intercorporeal and interaffective phenomenon where the sense-making process happens as both an individual and a joint process. This ongoing individual and participatory sense-making can further be understood as a reciprocal dependency between culture and self, where the students’ bodily learning process evolves on an existential level over time. Through this process, the students develop a sense of confidence and trust in each other, which creates a feeling of belonging. The educational potential of bodily learning through creating dance can be seen in relation to the affordances the students perceive and utilise within their learning culture in PETE.